The association of perceived stress score and quality of sleep in type 2 Diabetes mellitus patients at Hospital Pekan - Baharudin, Mohamad Sharul Fahmi; May, Khin Soe; Jamshed, Shazia Qasim; Abdul Rahim, Roslina; Win, Theingi; Andylim, Nizafaziasyida Fauzee; Mohd Mansor, Mohd Amin; Yaacob, Norhafiza; Ken, Fong Voon (2018)
Background: Type 2 diabetes mellitus (T2DM), a major worldwide cause of morbidity and mortality is mainly due to lifestyle factors and genetics. Physical and psychological stresses contribute to the development of hyperglycemia in the setting of T2DM. Sleep is essential for life. Glucose metabolism can be affected adversely by poor quality of sleep and less quantity of sleep. Excessive stress and sleep disturbances are the major barrier to effective glucose control and a danger to diabetic control. Thus, our study focused the corelation between stress and sleep that may be related to progression of disease in cases and controls. Objectives: The primary objective of the present study is to compare the perceived stress score (PSS) and quality of sleep between T2DM patients with healthy adults in Hospital Pekan, Pahang. Methods: A case control study was conducted at Diabetes Clinic in Pekan hospital. The Malay validation of Pittsburgh Sleep Quality Index (PSQI) and Perceived Stress Scale (PSS) questionnaire were prepared and contributed to volunteer subjects. Total volunteer participants 208 adults with ages ranged from 30- 70 years both genders were recruited; 104 had T2DM and 104 were healthy subjects. Descriptive analysis was done to compare two parameters by using SPSS version 21. Results: T2DM participants reported a higher amount of stress (48.93±2.92) compared to healthy subjects (28.51±4.28). Objectively measured in sleep quality was reflected by PSQI global scores in which T2DM experienced worsen sleep deprivation (7.31±2.02) in contrast with healthy adults (4.40±2.58). Both populations also had significant association of PSQI global and PSS factor scores (p<0.05). The study indicated that T2DM patients have poorer psychological wellbeing contrasting with control. Conclusions: Nobel finding of this study were evident in this sample size, these variables warrant further study.